New Moraxella Strain Isolated from Angular Conjunctivitis - van Bijsterveld, O. P. (1970)
A new Moraxella strain was isolated from angular conjunctivitis. It is characterized by the ability to produce acid from several carbohydrates, by its ability to produce indole, and by a lack of catalase activity.